Enhanced immobilization of chromium(VI) in soil using sulfidated zero-valent iron. (August 2019) - Guan, Xiaohong; Yang, Hongyi; Sun, Yuankui; Qiao, Junlian
Abstract: Batch tests were conducted in this study to evaluate the influence of sulfidation on the remediation of Cr(VI) in soil by zero-valent iron (ZVI). It was demonstrated that sulfidated ZVI synthesized by ball-milling with elemental sulfur (S-ZVI bm ) could reduce and immobilize Cr(VI) in soil more rapidly and efficiently than unamended ZVI (ZVI bm ). Specifically, with the optimal S/Fe molar ratio of 0.05 and ZVI dosage of 5 wt%, S-ZVI bm could completely sequestrate water soluble Cr(VI) (as high as 17.5 mg/L) within 3 h, while negligible Cr(VI) was reduced by ZVI bm over a 3-day incubation period under identical conditions. Furthermore, sequential extraction analysis revealed that S-ZVI bm treatment also promoted the conversion of exchangeable Cr to more stable forms (i.e., mainly as FeMn oxides bound fraction). XPS analysis showed that reduction was the main Cr(VI) remediation mechanism by ZVI, and alkaline extraction experiments further demonstrated Cr(VI) concentration in soil could be decreased from 153.6 mg/kg to 23.4 and 131.6 mg/kg by S-ZVI bm and ZVI bm, respectively. A magnetic separation process was introduced in this study to physically remove the residual ZVI particles and attached iron (hydr)oxides so as to minimize the re-release risk of immobilized Cr. Results revealed that, 71–89% of the added Fe and 9.5–33.6% of Cr could be retrieved from S-ZVI bm -treated soil. These findings highlighted the potential of S-ZVI bm as a promising amendment for immobilizing Cr(VI) in soil and the potential of magnetic separation as an alternative option for preventing the re-mobilization of sequestered Cr. Graphical abstract: Image 103581 Highlights: Sulfidation could significantly enhance Cr(VI) immobilization in soil by ZVI. The optimal S/Fe ratio and ZVI dosage were 0.05 and 5 wt%, respectively. S-ZVI bm promoted the conversion of exchangeable Cr to less mobile FeMn bound Cr. Magnetic separation after S-ZVI bm treatment could remove immobilized Cr from soil.